Analysis of technical efficiency in sweet potato production in the region of President Prudente - SP - Centeno Nakao, Daniela Capelas [UNESP]; Sabbag, Omar Jorge [UNESP]; Silva, Debora Pavani [UNESP]; Silva e Oliveira, Fagner Angelo [UNESP]; Menezes Candido de Paula, Glaucia Luciane Cham [UNESP]; Vargas, Pablo Forlan [UNESP] (Univ Fed Rural Pernambuco, Dept Administracao, 2020)
Sweet potatoes are a much-appreciated crop throughout the country and have several purposes, which can be used in food and feed, for the tissue, paper and cosmetics industries and for the production of biofuels. The Technical Efficiency Analysis by the Data Envelopment Analysis - DEA, allows to evaluate the efficiency of the sweet potato producers, to determine the most efficient through the practices adopted, serving as guidelines for the less efficient. The objective of this paper was to analyze the performance of sweet potato production units in the region of Presidente Prudente - SP, evaluating the degree of productive efficiency in relation to the contribution of each input and strategies used in the cropping systems. Methodologically, in November 2018, 12 sweet potato producers in the region of Presidente Prudente/SP were interviewed, using a questionnaire composed of open and closed questions. From the data collected, five variables were selected, four corresponding to inputs or factors of production, and one related to the product (output). With the aid of the SIAD software - version 3.0 (Integrated Decision Support System), it was possible perform the DEA and evaluate the efficiency of the sweet potato production units. The main results show that the overall average efficiency obtained between the production units was 90%, and only two units were in the efficiency class of 71% to 80%, which have a higher operating cost and use a larger surplus of work hours to produce. The labor and area inputs are the ones that most express variability and directly influence the efficiency of some producers, making it necessary to optimize these variables. It is concluded that this multicriterial analysis technique assists in the decision-making process during the production process, and can serve as a complementary model to other forms of management assessment applied to Brazilian horticulture.
Keywords: DEA analysis; Productive units; Performance; Viability